Healthy males’ antioxidant system response in induced acute hyperglycemia - Oré, Raquel (2009)
Objective: To determine healthy males’ antioxidant system response in induced acute hyperglycemia. Design: Prospective, descriptive, longitudinal, experimental study. Setting: National Institute of Andean Biology, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biological materials: Whole blood and serum of apparently healthy men. Interventions: After 10 hour fasting, intravenous glucose was administered to thirteen healthy 20-41 year-old adult men using the hyperglycemic clamp method at 125 mg/dL above basal value during 120 minutes. Glycemia was measured at 0, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, and 120 minutes. Blood sampling was obtained with EDTA anticoagulant and whole blood to obtain blood serum for biochemistry tests at 0, 60 and 120 minutes. Main outcome measures: Blood serum glycemia and lipoperoxidation variation, glutathione and superoxide dismutase activity in lysed red blood cells and oxidative stress index. Results: After achieving ‘balance’, glucose levels during hyperglycemic clamp was 197 ± 17,58 mg/dL. Lipoperoxidation increased from 2,54 + 0,51 to 2,90 + 0,58umol/L, from 0 to 60 minutes, and to 2,66 + 0,55 umol/L at 120 minutes. Glutathione was reduced in 8,10% at one hour, rising 7,08% at 120 minutes. Superoxide dismutase activity rose above basal 0,54% at 60 min and 5,66% at 120 min. Oxidative stress valuation index had high level to very high level positive Pearson r correlation. Conclusions: Acute induced hyperglycemia up to 2 hours increased oxidative stress, promoting generation of antioxidant defence with de novo synthesis of reduced glutathione and greater activity of superoxide dismutase.